Land Conflict and Social Movement of Local Community: A Study in Jambi Province - Muliono Muliono; Citra Darminto; Mariatul Qibtiyah (Universitas Pendidikan Ganesha, 2025)
This research discusses land conflicts and social movements organized by local communities to fight for the rights they have long been entitled to. Land conflict is one of the largest type of conflict in Jambi and Indonesia in general. The implications of the conflict are extremely considerable for the local communities both physically and psychologically. This research uses qualitative. The data were obtained through observations, interviews and FGDs. Data processing based on three processes namely reducing, verifying, and displaying data. The data analysis refers to relative deprivation and Dahrendorf perspective. The results show that, firstly, there is a series of complexities involving various actors’ interests and overlapping policies caused this conflict occurs. Secondly, the resistance emerges as a response of relative deprivation to the condition allowing the “perpetuation” of land ownership claims. The lack of common ground between state, corporation and indigenous people means that the only way for the local communities to respond is by organizing social movements. Thirdly, although these movements face a strong challenge which is not easy to rip off, this study confirms that social movement is a way for local communities to reveal the layered dynamics of exclusion and the myriad factors contributing to the marginalization of local community's land ownership.